Emperor of thorns - Lawrence, Mark, 1966- (Lawrence, Mark, 1966- Broken empire, 2014)
Desiring to be emperor of the Broken Empire, young King Jorg Ancrath of the seven nations must face an adversary standing in his way, a necromancer unlike any he has ever challenged -- a figure hated and feared even more than himself: the Dead King.